Menakar Justice for Peace dalam Penyelesaian Sengketa Konsumen Melalui Mediasi (Studi Keputusan BPSK No. Reg. 004/REG/BPSK-DKI/I/2016) - Mia Hadiati; Mariske Myeke Tampi (Jurnal Hukum IUS QUIA IUSTUM, 2018)
Consumers and business actors as seekers for justice for peace consider the decision of the Consumer Dispute Resolution Agency (BPSK) as a peace agreement letter containing the values of justice for peace. The problem analyzed in this research was the achievement of justice for peace in the decision of BPSK in Jakarta in decision No. Reg. 004/REG/BPSK-DKI/I/2016 dated January 22, 2016 between Andhie Saad as a consumer and Turkish Airlines as a business actor based on the principles of justice, benefit, and legal certainty. This research used qualitative method with statute approach and conceptual approach based on theories of Jeremy Bentham, John Rawls and Hans Kelsen as elements of justice for peace. The primary legal materials used were Law no. 8 of 1999 on Consumer Protection and Decree of the Minister of Industry and Trade of the Republic of Indonesia No. 350/MPP/Kep/12/2001 on the Implementation of Duties and Authority of Consumer Dispute Resolution Agency (BPSK). The analysis was carried out using philosophical-normative approach. The result of the research showed that, the resolution of Consumer Dispute through Consumer Dispute Resolution Agency (BPSK) in decision of BPSK No. Reg.004/REG/BPSK-DKI/I/2016 has met the values of justice for peace.